The Political Theory of Conservative Economists - Waligorski, Conrad P. (University Press of Kansas, 1990)
It's difficult to overstate the impact of conservative economics on American life. The conservative thought of economists like Milton Friedman, James Buchanan, and Friedrick Hayek has provided the conceptual framework that undergirds nearly every aspect of current U.S. socialeconomic policy. Although a great deal has been written about the economic theories of these Nobel Prizewinning economists, this study is the first to examine the political theory that underlies conservative economics and its implications for public policy.Long associated with the "Chicago" and "public choice" schools of thought, Friedman, Buchanan, Hayek, and others have consistently repudiated Keynesian principles. They have steadfastly opposed social welfare policies and regulation of private enterprise, championing instead the free market as a mechanism for ordering society.In this book Conrad Waligorski analyzes the political content of the conservative economists' arguments. In so doing, he illuminates the political, economic, and philosophical ideas behind and justification for the laissezfaire policy-the reduced regulation, intervention, and welfare favored by conservative governments in the United States, Canada, and Britain.